Budaya Digital Islami dalam Menyikapi Fenomena Hate speech di Media Sosial Instagram - Amelia Putri; Nur Rizky Awaliyah; Raden Muhammad Hilmi Maulana (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2026)
The development of Instagram as a digital communication tool has brought about significant changes in people’s interaction patterns. However, the high use of social media has also given rise to various problems, one of which is the phenomenon of hate speech, which can trigger social conflict, division, and a decline in communication ethics in the digital space. This study aims to analyze Islamic digital culture in responding to the phenomenon of hate speechon Instagram and to understand the application of Islamic values in building polite and responsible communication. The method used in this research is a qualitative literature study approach, namely by collecting data from various journals and scientific articles, as well as previous research relevant to the topic. The results show that Islamic digital culture emphasizes the importance of maintaining communication ethics, implementing tabayyun (reconciliation), avoiding hate speech, and prioritizing the values of tolerance and mutual respect in the use of social media. In addition, self-control and digital literacy based on Islamic values are important factors in creating a healthy and harmonious digital environment. This study implies that the application of Islamic digital culture can be a solution in reducing the spread of hate speechon Instagram.